2020
DOI: 10.1177/0268355520975582
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava filters utilization in patients with venous thromboembolism: Analysis of a database of a tertiary hospital

Abstract: Purpose The aim of the study was to assess the inferior vena cava filter (IVCF) utilization in patients with venous thromboembolism (VTE) in tertiary care. Methods We performed a retrospective analysis of database of a tertiary hospital in 2016–2017. All the records of patients admitted for VTE or diagnosed with VTE being hospitalized for other reasons were extracted. The data collected were number of patients, who received IVCF, indications to filter insertion, PE and death rate after procedure, frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 8 , 9 Among all patients with VTE, up to 20-40% in the USA and up to 20% in Russia undergoing IVC filter implantation. 10 - 12 Since retrievable filters were introduced several decades ago, their current removal rate is not high enough, estimated from 34% to 45%. 13 , 14 Thus, a lot of patients require anticoagulation in the presence of IVC filter, which raised concern about the reliability of direct oral anticoagulants (DOACs) in such circumstances.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Among all patients with VTE, up to 20-40% in the USA and up to 20% in Russia undergoing IVC filter implantation. 10 - 12 Since retrievable filters were introduced several decades ago, their current removal rate is not high enough, estimated from 34% to 45%. 13 , 14 Thus, a lot of patients require anticoagulation in the presence of IVC filter, which raised concern about the reliability of direct oral anticoagulants (DOACs) in such circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Both DVT and PE are collectively referred to as venous thromboembolism (VTE) (Yamashita et al, 2022). Currently, systemic anticoagulation is still the preferred method of prevention for VTE OPEN ACCESS EDITED BY Yang Liu, Hong Kong Polytechnic University, Hong Kong SAR, China patients with underlying PE (Duffett and Carrier, 2017;Arslanbekov et al, 2021;Elias et al, 2021). Recent studies have shown that there is no additional benefit of IVCFs deployment in VTE patients with better anticoagulation therapy (Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%